2003
DOI: 10.1002/jcc.10299
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of the mechanism of the atmospheric reaction: NO2 + O3 → NO3 + O2

Abstract: The atmospheric reaction NO2 + O3 --> NO3 + O2 (1) has been investigated theoretically by using the MP2, G2, G2Q, QCISD, QCISD(T), CCSD(T), CASSCF, and CASPT2 methods with various basis sets. The results show that the reaction pathway can be divided in two different parts at the MP2 level of theory. At this level, the mechanism proceeds along two transition states (TS1 and TS2) separated by an intermediate, designated as A. However, when the single-reference higher correlated QCISD methodology has been employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…The Δ 17 O(O 3 *) value thus obtained is relevant to other bimolecular reactions incorporating in their products the same reactive O-atom of ozone (i.e., reactions involving the same transfer mechanism as the O 3 + NO 2 reaction). [39] It is therefore highly relevant to the study of the propagation of the Δ 17 O(O 3 ) through atmospheric reactions. [21,23,40] Reagent preparation and filter coating procedure…”
Section: Methodsmentioning
confidence: 99%
“…The Δ 17 O(O 3 *) value thus obtained is relevant to other bimolecular reactions incorporating in their products the same reactive O-atom of ozone (i.e., reactions involving the same transfer mechanism as the O 3 + NO 2 reaction). [39] It is therefore highly relevant to the study of the propagation of the Δ 17 O(O 3 ) through atmospheric reactions. [21,23,40] Reagent preparation and filter coating procedure…”
Section: Methodsmentioning
confidence: 99%
“…Ab initio calculations on the mechanism of the reaction NO 2 +O 3 reveal that it proceeds through the abstraction of the terminal O atom of ozone (Peìro-Garcìa and Nebot-Gil, 2003). In addition, the transfer of 17 O through reaction NO 2 +O 3 has been recently studied in the lab and it was also concluded that only the terminal O atom of ozone is transferred (Berhanu and Bhattacharya, personal communication, 2011).…”
Section: O(o 3 )mentioning
confidence: 99%
“…29 Based on ab initio studies, the reaction of NO 2 with O 3 seems to be determined by the π orbital of the terminal oxygen atom of ozone. 30 Accordingly, NO 2 attacks the terminal oxygen of ozone and forms a single transition state (TS1), the rate-determining step. On the contrary, the NO + O 3 reaction proceeds through two transition states (TS1 and TS2) as well as an intermediate (A).…”
Section: A Reaction Dynamicsmentioning
confidence: 99%
“…On the contrary, the NO + O 3 reaction proceeds through two transition states (TS1 and TS2) as well as an intermediate (A). 30,31 Application of the singlereference higher correlated quantum configuration interaction with single and double excitation methodology (QCISD) (Ref. 30) for the computation of the reaction mechanism in case of NO 2 + O 3 shows that the overall reaction is a direct process with no intermediate (A) and transition state TS2.…”
Section: A Reaction Dynamicsmentioning
confidence: 99%